Onyx embolization in distal dissecting posterior inferior cerebellar artery aneurysms. (2nd April 2015) - Puri, Ajit S; Massari, Francesco; Hou, Samuel Y; Lozano, Juan Diego; Howk, Mary; Perras, Mary; Brooks, Christopher; Gounis, Matthew J; Kan, Peter; Wakhloo, Ajay K
Abstract : Background: Dissecting aneurysms located along the distal segments of the posterior inferior cerebellar artery (PICA) are extremely rare, accounting for only 0.5–0.7% of all intracranial aneurysms. Treatment of these aneurysms is challenging, both surgically and endovascularly. We present our preliminary experience and clinical data utilizing Onyx as an embolization agent in the treatment of these lesions with proximal parent artery preservation. Methods: 7 consecutive ruptured peripheral PICA aneurysms, in 7 patients, were treated with superselective Onyx embolization at our institutions. According to the anatomical classification of Lister et al, these aneurysms were located in the lateral medullary segment (n=1), tonsillomedullary segment (n=1), and the telovelotonsillary segment (n=5) of the PICA. Technical feasibility, procedure related complications, angiographic results, follow-up diagnostic imaging, and clinical outcome were evaluated. Results: In all cases, endovascular treatment was successful, with complete occlusion of the aneurysm with proximal parent artery preservation at the final postprocedural angiogram. Procedure related complications were not observed. One patient with a poor clinical condition at admission died during the initial hospital stay due to extensive subarachnoid and intraventricular hemorrhage. No rebleeding or recanalization was noted during follow-up. Two patients had a residual moderate to severe disability at follow-up. Favorable outcomes, with no or mild disability, were observed in four of the surviving patients. Conclusions: Angiographic, diagnostic imaging, and clinical results of our small series indicate that Onyx embolization of dissecting distal PICA aneurysms with parent artery preservation is an effective option with acceptable morbidity and mortality rate, in those cases in which surgical clipping or endovascular coiling of the aneurysmal sac is not suitable.